A review of photovoltaic water pumping system designing methods, control strategies and field performance. (February 2017) - Muhsen, Dhiaa Halboot; Khatib, Tamer; Nagi, Farrukh
Abstract: Photovoltaic water pumping system (PVPS) is an important and promising application of solar energy systems especially in remote areas. In this review paper, research work on PVPS modeling, reliability, feasibility, field performance, design procedures and control strategies is analyzed and reported. In addition, technical challenges to this science are concluded in this review. According to the results, the numerical method is recommended for sizing PVPS. In the meanwhile, incremental conductance and artificial intelligent (AI) based maximum power point tracking algorithms are the most recommended control strategies for PVPS. On the other hand, According to reported PVPS performance, the average overall system's efficiency is about 3.4% with average annual productivity rate of 6580.611 m 3 /kWp. In general PVPS have a number of challenges related to design procedure, modeling method, control strategy, availability of data and site obstacles such as shadow effects.